Media Studies in School Curriculum : Obstacles, Challenges and Possibilities - Yadav, Anubhuti (JOURNAL OF INDIAN EDUCATION, 2011)
Media studies as a subject has at last entered the boundaries of schools though little late. Disregarding media from the school curriculum has always bothered many experts who are working in the field of media studies. Many initiatives were undertaken to introduce children, parents and teachers to the concepts of media studies but all happened out of the schools. One of the key point made by the NCF, 2005, i.e., connecting knowledge to the life outside the school, has actually opened the door for media studies, a subject which has never in the past was given its due importance in school curriculum. It was realised that students’ media experiences are as important as their experience with their parents, peers and teachers, and by allowing them to bring their media experiences in classroom, a creative environment can be created where they could get a chance to discuss issues which are very integral to their life. This paper focuses on why media should be a part of school curriculum, how it can be introduced, the present scenario, challenges it can face and some strategies to overcome those challenges.